Comprehensive Reward System, Employee Motivation and Turnover Intention: Evidence from Nepali Banking Industry (Quest Journal of Management and Social Sciences, 2019)
Background: Employee motivation and employee turnover are  central issues in the modern organizations as human capital is the most important intangible asset for organizational productivity. Attitude, skills and knowledge of employees create the competitive advantage of the organization. It is the growing challenge for retaining competent and professional employees in the organization within the increasing global opportunities. Employee motivation, satisfaction, job burnout, turnover are being common challenges to the management. To cope with such challenges, organizations should have strategic focus on comprehensive reward system.Objectives: This study aims at  exploring the factors of comprehensive reward system. More specifically, relationships between the components of comprehensive reward system and employee motivation are examined. Finally, the impact of employee motivation derived from reward system was tested with employee turnover intention.Methods: This study was conducted with descriptive-correlational research design that follows quantitative approach. Primary data for each variable was collected from 200employees holding different positions in different banks. A 5-Point Likert Scale was used to collect major responses on the variables. Descriptive statistics, Pearson correlation, and regression analysis were used to test the hypothesis. Inferences were made on five per cent and one per cent level of significance.Result: Results of the study revealed that compensation, benefits, work-life balance, performance recognition and empowerment and career opportunity were the major factors as the components of comprehensive reward system. It was found that these factors had significant positive relationship with employee motivation. Results also revealed the negative significant relationship between employee motivation and their turnover intention.Conclusion: Employees of Nepali banking industry strongly believe in comprehensive reward system ranging from economic benefits to the personal growth. It is also concluded, with supporting the theory that employee motivation helps to solve the employee turnover intention.Implications: To solve the high corporate movement of employees in Nepali banks, this study provides a key insight for focusing on comprehensive reward system.